THE LEGAL NATURE OF THE INSTITUTION OF PRE-TRIAL SETTLEMENT OF DISPUTES ARISING FROM PUBLIC RELATIONS - Tulepbaeva , Анджела Сериковна; Makenov , Тимур Канатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The institution of pre-trial settlement of disputes arising from public relations, as a mechanism for protecting the rights and legitimate interests of citizens and organizations, plays a huge role in building an effective dialogue between government bodies and individuals and legal entities that contribute to increasing confidence in public authority and the legal system of the state as a whole. However, despite its importance, the institution of pre-trial settlement of public disputes has not been adequately reflected in the legislation of the Republic of Kazakhstan. In particular, it is necessary to further improve the procedure for appealing by individuals and legal entities of decisions and actions (inaction) of government officials, the introduction of new concepts. The article briefly reviews the history of the emergence of the institution of pre-trial settlement of disputes arising from public relations, carried out a theoretical analysis of the concept, describes the functions and features of the institution of pre-trial settlement of public disputes. As part of the administrative reform carried out by the Republic of Kazakhstan, including aimed at improving the legislation governing pre-trial appeal, and also in connection with the expansion of the concept of the institution of pre-trial settlement of disputes arising from public relations, the author suggests defining its concept at the legislative level and incorporating it into the draft Administrative Procedure Code of the Republic of Kazakhstan. The definition of the concept of pre-trial settlement of disputes arising from public relations would exclude the possibility of its different interpretation and application.